Cohesin SA1 and SA2 are RNA binding proteins that localize to RNA containing regions on DNA. Issue 10 (30th April 2020) - Pan, Hai; Jin, Miao; Ghadiyaram, Ashwin; Kaur, Parminder; Miller, Henry E; Ta, Hai Minh; Liu, Ming; Fan, Yanlin; Mahn, Chelsea; Gorthi, Aparna; You, Changjiang; Piehler, Jacob; et al.
Abstract: Cohesin SA1 (STAG1) and SA2 (STAG2) are key components of the cohesin complex. Previous studies have highlighted the unique contributions by SA1 and SA2 to 3D chromatin organization, DNA replication fork progression, and DNA double-strand break (DSB) repair. Recently, we discovered that cohesin SA1 and SA2 are DNA binding proteins. Given the recently discovered link between SA2 and RNA-mediated biological pathways, we investigated whether or not SA1 and SA2 directly bind to RNA using a combination of bulk biochemical assays and single-molecule techniques, including atomic force microscopy (AFM) and the DNA tightrope assay. We discovered that both SA1 and SA2 bind to various RNA containing substrates, including ssRNA, dsRNA, RNA:DNA hybrids, and R-loops. Importantly, both SA1 and SA2 localize to regions on dsDNA that contain RNA. We directly compared the SA1/SA2 binding and R-loops sites extracted from Chromatin Immunoprecipitation sequencing (ChIP-seq) and DNA-RNA Immunoprecipitation sequencing (DRIP-Seq) data sets, respectively. This analysis revealed that SA1 and SA2 binding sites overlap significantly with R-loops. The majority of R-loop-localized SA1 and SA2 are also sites where other subunits of the cohesin complex bind. These results provide a new direction for future investigation of the diverse biological functions of SA1 and SA2.